Immunosensor of Nitrofuran Antibiotics and Their Metabolites in Animal-Derived Foods: A Review - Jia, Jingze; Zhang, Hongxia; Qu, Jiayi; Wang, Yuanfeng; Xu, Naifeng (Frontiers in Chemistry, 2022)
Nitrofuran antibiotics have been widely used in the prevention and treatment of animal diseases due to the bactericidal effect. However, the residual and accumulation of their metabolites in vivo can pose serious health hazards to both humans and animals. Although their usage in feeding and process of food-derived animals have been banned in many countries, their metabolic residues are still frequently detected in materials and products of animal-derived food. Many sensitive and effective detection methods have been developed to deal with the problem. In this work, we summarized various immunological methods for the detection of four nitrofuran metabolites based on different types of detection principles and signal molecules. Furthermore, the development trend of detection technology in animal-derived food is prospected.